CrAssphage as a Human Enteric Viral Contamination Bioindicator in Marketed Bivalve Mollusks - Isabella Rodrigues Negreiros; Natália Lourenço dos Santos; Bruna Barbosa de Paula; Bruna Lopes Figueiredo; Marcelo Luiz Lima Brandão; José Paulo Gagliardi Leite; Marize Pereira Miagostovich; Carina Pacheco Cantelli (Viruses, 2025)
CrAssphage, a bacteriophage that infects human gut-associated Bacteroides spp., has emerged as a potential anthropogenic fecal pollution indicator in environmental matrices. This study investigated the presence and concentration of crAssphages in bivalve mollusks (oysters and mussels) marketed in three cities in the state of Rio de Janeiro, Brazil, sampled from January to December 2022. CrAssphages were detected during the study period in 66.7% (48/72) of sampled oysters and 54.8% (34/62) of sampled mussels, at median concentrations of 1.9 × 104 and 4.2 × 104 genome copies (GC)/g, respectively. These levels were 1–2 log10 higher than those observed for major human enteric viruses, including norovirus genogroups GI and GII, sapovirus, human mastadenovirus (HAdV), rotavirus A, human astrovirus (HAstV), and hepatitis A virus. CrAssphage specificity and sensitivity were calculated for all viruses. Moderate correlations between crAssphage (log10 GC/g) and norovirus GI and GII, HAdV, SaV, and HAstV (Spearman’s rho = 0.581–0.464, p < 0.001) were observed in mussels. Altogether, the data support the use of crAssphage as a molecular indicator of human viral contamination in shellfish, with potential application in routine environmental and food safety monitoring in production areas.